Review on the optimal placement, sizing and control of an energy storage system in the distribution network - Wong L.A.; Ramachandaramurthy V.K.; Taylor P.; Ekanayake J.B.; Walker S.L.; Padmanaban S. (Elsevier Ltd, 2023)
Artificial intelligence; Electric power distribution; Energy storage; Renewable energy resources; Energy storage systems; Future improvements; Literature reviews; Objective functions; Optimal allocation; Optimal placements; Renewable energy based generations; Renewable energy generation; Data storage equipment